The Norwegian Adaptation of the Big Five Inventory-2 - Føllesdal, Hallvard; Soto, Christopher J. (Frontiers in Psychology, 2022)
Two studies were conducted to assess the psychometric properties of scores from the Norwegian adaptation of the Big Five Inventory-2 (BFI-2). In Study 1, the BFI-2 was translated to Norwegian and the scores from a convenience sample (N = 606) demonstrated good psychometric properties. BFI-2 scores from subsamples correlated in expected ways with self- and other ratings of the Big Five, and with self-ratings of empathic concern and perspective taking. In Study 2, after some minor improvements in translation, the psychometric properties of BFI-2 scores were assessed in a new sample (N = 409). Results from random intercept EFA of scores supported the proposed model. The psychometric properties of two shorter versions of the inventory, the BFI-2-S and BFI-2-XS, were also examined. Overall, the results suggest that the Norwegian adaptation of the BFI-2 provide reliable and valid scores.